EVALUATION OF PHYSICO-CHEMICAL PARAMETERS OF DIFFERENT SHODHIT GUGGUL - Patel, Mayuree A.; Acharya, Sanjeev R; Macwan, Carol P.; Patel, Tejas B.; Suhagia, B. N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present study was aimed to identify the physicochemical data of shodhit guggul. Guggul is a gum-resin exudate from the plant Commiphora weightii (Arn.) Bhandari, belonging to Burseraceae family. In Ayurveda, guggul is always purified. This purification is known as Shodhan. Shodhan is a process by which guggul is made non-toxic, effective, suitable and fit for therapeutic purposes. Methods: The seven different shodhan dravya were used to prepare shodhit guggul. They were evaluated by performing physicochemical parameters including five different extractive value; total ash, acid insoluble, water soluble and sulphated ash value; pH, and loss on drying. Results: Analytical results of raw guggul showed total ash, acid insoluble ash, water soluble ash and sulphated ash value to 5.36±0.04%, 0.96±0.03%, 4.51±0.03 % and 8.40±0.04% respectively. These all values of each shodhit guggul were different. The extractive value of raw guggul was comparable with standard value while the extractive value of each shodhit guggul was totally different. The pH value of 1% w/v and 10% w/v aqueous solution of raw guggul was 6.44±0.18 though pH of each shodhit guggul was changed. The loss on drying of raw guggul was found to be 1.88±0.02%w/v, however, this value was different for each shodhit guggul. Conclusion: The present study revealed that the different shodhan process with specific shodhan dravya affects the physicochemical parameters. The analysis and comparison of the data showed the difference in the properties of seven shodhit guggul with respect to raw Guggul.